Ecology and biodiversity of benthos - Godson, Prince S.; Vincent, Salom Gnana Thanga; Krishnakumar, S. (Elsevier, 2022)
"Ecology and Biodiversity of Benthos provides insights into the characteristic features of marine and estuarine benthos that play an important role in coastal ecosystem functioning, a primary level in the food chain. The book provides the latest information on multidisciplinary reflections by various researchers studying the benthic community. Through the chapters, ecosystem services are explored as a way to share approaches and scientific methods to achieve knowledge-based sustainable planning and management of benthic ecosystems. This is a helpful guide for anyone working on marine and estuarine environments, and for those who need an introduction to benthic ecology. The book has a wide range of scientific coverage since it caters primarily to the requirement of marine ecologists, marine benthologists, EIA experts, aquatic researchers, scientists, teachers and research scholars. In addition to this, it also serves as a reference for postgraduate/undergraduate students studying aquatic ecosystems."--Publisher website.